Credit-based fair queueing (CBFQ): a simple service-scheduling algorithm for packet-switched networks - Bensaou, B.; Tsang, D.H.K.; King Tung Chan (IEEE/ACM transactions on networking, 2001)
This paper proposes a simple rate-based scheduling algorithm for packet-switched networks. Using a set of counters to keep track of the credits accumulated by each traffic flow, the bandwidth share allocated to each flow, and the size of the head-of-line (HOL) packets of the different flows, the algorithm decides which flow to serve next. Our proposed algorithm requires on average a smaller complexity than the most interesting alternative ones while guaranteeing comparable fairness, delay, and delay jitter bounds. To further reduce the complexity, a simplified version (CBFQ-F) of the general algorithm is also proposed for networks with fixed packet lengths, such as ATM, by relaxing the fairness bound by a negligibly small amount.